Chitosan-based Colloidal Polyelectrolyte Complexes for Drug Delivery: A Review. (15th June 2020) - Wu, Danjun; Zhu, Lixi; Li, Yi; Zhang, Xueling; Xu, Shumin; Yang, Gensheng; Delair, Thierry
Highlights: Parameters impacting the formation of chitosan-based colloidal polyelectrolyte complexes (PECs) are reviewed. Chitosan-based nanoPECs towards the mucosal delivery, cancer therapy, gene delivery and anti-HIV therapy are highlighted. Challenges and future perspectives on the applications of chitosan-based nanoPECs are emphasized and co mmented. Abstract: Polyelectrolyte complexes (PECs) as safe drug delivery carriers, are spontaneously formed by mixing the oppositely charged polyelectrolyte solutions in water without using organic solvents nor chemical cross-linker or surfactant. Intensifying attentions on the PECs study are aroused in academia and industry since the fabrication process of PECs is mild and they are ideal vectors for the delivery of susceptible drugs and macromolecules. Chitosan as the unique natural cationic polysaccharide, is a good bioadhesive material. Besides, due to its excellent biocompatibility, biodegradability, abundant availability and hydrophilic nature, chitosan-based PECs have been extensively applied for drug delivery, particularly after administration through mucosal and parenteral routes. The purpose of this review is to compile the recent advances on the biomedical applications of chitosan-based PECs, with specific focuses on the mucosal delivery, cancer therapy, gene delivery and anti-HIV therapy. The challenges and the perspectives of the chitosan-based PECs are briefly commented as well.